Titanium material for manufacturing metal foil, manufacturing method of titanium material for manufacturing metal foil, and drum for manufacturing metal foil

JP7633540B2Active Publication Date: 2025-02-20NIPPON STEEL CORPORATION
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022539801
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-07-27
Publication Date
2025-02-20
Estimated Expiration
2040-07-27

AI Technical Summary

Benefits of technology

【0016】 以上説明したように本発明に係る上記態様よれば、金属箔製造用チタン材を金属箔製造用のドラムに使用した際にマクロ模様の発生を抑制することが可能となる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007633540000029
    Figure 0007633540000029
  • Figure 0007633540000030
    Figure 0007633540000030
  • Figure 0007633540000031
    Figure 0007633540000031
Patent Text Reader

Abstract

A titanium material according to the present invention has a ratio of 0.95-1.05 of voltages in two neighboring locations from among a plurality of locations when a pair of conductive electrode probes are brought into contact and a rated voltage is supplied, a pair of potential detection probes are brought in contact with a surface, with a fixed probing distance therebetween, and the voltage of the plurality of locations on the surface is measured.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a titanium material for use in producing metal foil, a method for producing a titanium material for use in producing metal foil, and a drum for producing metal foil. [Background technology]

[0002] Copper foil is often used as a raw material for the wiring of wiring boards such as multilayer wiring boards and flexible wiring boards, and for conductive parts of electronic components such as current collectors in lithium ion batteries.

[0003] Copper foils for such applications are manufactured, for example, by the following method. Drums with a width of 1 m or more and a diameter of several meters, made of insoluble metals such as lead and titanium, serving as anodes and cathodes, are placed in a copper sulfate solution in which copper raw materials are dissolved in a sulfuric acid solution, and copper is continuously electrodeposited onto the drum while rotating. The deposited copper is continuously peeled off and wound into a roll. In this manner, copper foil is manufactured.

[0004] Titanium is generally used as the material for the drum because of its excellent corrosion resistance and excellent peelability of the copper foil. However, even if titanium material with excellent corrosion resistance is used, the surface of the titanium material constituting the drum is gradually corroded in the copper sulfate solution when copper foil is produced over a long period of time. The state of the drum surface affected by corrosion is transferred to the copper foil during the production of the copper foil.

[0005] It is known that the corrosion state and the degree of corrosion of metal materials vary depending on various internal factors caused by the metal structure of the metal material, such as the crystal structure, crystal orientation, defects, segregation, processing distortion, and residual distortion. When a drum made of a metal material with a heterogeneous metal structure between parts is affected by corrosion during the production of copper foil, the homogeneous surface state of the drum cannot be maintained, and a heterogeneous surface occurs on the drum surface. The heterogeneous surface that occurs on the drum surface can be identified as a pattern. Among the patterns caused by such heterogeneous metal structures, a pattern that is caused by a macro structure with a relatively large area and can be distinguished by the naked eye is called a "macro pattern". The macro pattern that occurs on the drum surface can also be transferred to the copper foil during the production of the copper foil.

[0006] Therefore, in order to manufacture copper foil with high precision and uniform thickness, it is important to homogenize the metal structure of the titanium material constituting the drum and achieve uniform corrosion of the drum, thereby reducing macroscopic patterns caused by non-homogeneous macroscopic structures.

[0007] Patent Document 1 proposes a titanium sheet for use in drums for producing electrolytic Cu foil, which contains, by mass%, Cu: 0.15% or more and less than 0.5%, oxygen: more than 0.05% and less than 0.20%, Fe: 0.04% or less, with the remainder being titanium and unavoidable impurities, in order to suppress macroscopic patterns, and is characterized by having an α-phase homogeneous fine recrystallized structure with an average crystal grain size of less than 35 μm.

[0008] Patent Document 2 proposes a titanium sheet for use in drums for producing electrolytic Cu foil, which contains, by mass%, 0.3 to 1.1% Cu, 0.04% or less Fe, 0.1% or less oxygen, and 0.006% or less hydrogen, has an average grain size of 8.2 or more, and has a Vickers hardness of 115 to 145, and has a texture in a region parallel to the sheet surface, in which, in a (0001) plane pole figure of the α phase from the normal direction (ND axis) to the rolled surface, the inclination angle of the normal to the (0001) plane is an ellipse with a major axis of ±45° in the rolling width direction (TD) and a minor axis of ±25° in the final rolling direction (RD), where A is the total area of ​​crystal grains present within the range of the ellipse and B is the total area of ​​other crystal grains, with an area ratio A / B of 3.0 or more. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Japanese Patent Publication No. 2009-41064 [Patent Document 2] Japanese Patent Publication No. 2012-112017 Summary of the Invention [Problem to be solved by the invention]

[0010] However, the titanium plate for electrolytic Cu foil manufacturing drum described in Patent Document 1 or Patent Document 2 contains elements such as Fe that are easily distributed to the liquid phase side during the solidification process when manufacturing the titanium plate. Therefore, the chemical composition of the titanium plate is likely to segregate, that is, vary. If the chemical composition varies, the titanium plate may corrode unevenly during the metal foil manufacturing process, causing a macro pattern on the titanium plate, which may be transferred to the manufactured metal foil.

[0011] The present invention has been made in consideration of the above problems, and an object of the present invention is to provide a titanium material for producing metal foil, a method for producing titanium material for producing metal foil, and a metal foil production drum that are capable of suppressing the occurrence of macroscopic patterns when used in a drum for producing metal foil. [Means for solving the problem]

[0012] The present inventors have focused on the fact that the occurrence of macroscopic patterns present on metal foil production drums in an as-polished state, and macroscopic patterns associated with non-uniform corrosion during use, is influenced by various internal quality factors resulting from the metal structure, such as the chemical composition of the metal material, crystal structure, crystal orientation, defects, segregation, processing strain, residual strain, etc. They have then discovered that the occurrence of macroscopic patterns is suppressed when the electrical resistance at each site on the surface of a titanium material for metal foil production satisfies certain conditions, leading to the present invention.

[0013] The gist of the present invention, which has been completed based on the above findings, is as follows. (1) The first aspect of the present invention is, in mass %, Sn: 0% or more and 2.0% or less, Zr: 0% or more and 5.0% or less, Al: 0% or more and 7.0% or less, N: 0% or more and 0.100% or less, C: 0% or more and 0.080% or less, H: 0% or more and 0.0150% or less, O: 0% or more and 1.000% or less, Fe: 0% or more and 0.500% or less, Cr: 0% or more and 0.500% or less, Ni: 0% or more and 0.090% or less, Cu: 0% or more and 1.5% or less, and Mo: 0% or more and 0.750% or less, The balance has a chemical composition including Ti and impurities, The total content of Fe, Cr, and Ni is 0% or more and 0.500% or less, one A pair of current-carrying electrode probes are brought into contact to supply a constant current; and The probe spacing is 125 times the average grain size and 67 mm or less. This titanium material for manufacturing metal foil has a voltage ratio of 0.95 or more and 1.05 or less between two adjacent points on the surface when a pair of potential detection probes is brought into contact with the surface with a fixed probe spacing and the voltages of the multiple points on the surface are measured. (2) The titanium material for manufacturing metal foil described in (1) above has, in mass%, N: 0% or more and 0.100% or less, C: 0% or more and 0.080% or less, H: 0% or more and 0.0150% or less, O: 0% or more and 0.400% or less, Fe: 0.02% or more and 0.500% or less, Ni: 0% or more and 0.090% or less, and Cu: May be contained in an amount of 0% or more and 1.5% or less. (3) The titanium material for manufacturing metal foil described in (1) above contains Fe, Cr, Ni, and Mo, The Ni content is 0.090 mass% or less, The content of Mo may be 0.5 to 1.2 times the total content of Fe, Cr, and Ni, on a mass basis. (4) The titanium material for manufacturing metal foil described in (1) above has, in mass %, Sn: 0.2% or more and 2.0% or less, Zr: 0.2% or more and 5.0% or less, and Al: 0.2% or more and 3.0% or less, one or more of the group consisting of, is contained in a total amount of 0.2% or more and 5.0% or less, N: 0% or more and 0.100% or less, C: 0% or more and 0.080% or less, H: 0% or more and 0.0150% or less, O: 0% or more and 1.000% or less, and Fe: May be contained in an amount of 0% or more and 0.500% or less. (5) The titanium material for manufacturing metal foil described in (1) above contains Al in an amount of more than 1.8% by mass and not more than 7.0% by mass, When the Al content is [Al%], the Zr content is [Zr%], the Sn content is [Sn%], and the O content is [O%] in mass%, the following formula (1) is satisfied: Aleq=[Al %]+[Zr %] / 6+[Sn %] / 3+10×[O %] The Al equivalent Aleq represented by formula (1) may be 7.0 mass % or less. (6) The titanium material for use in producing a metal foil according to any one of the above (1) to (5) may be a titanium material for use in a drum for producing a metal foil.

[0014] (7) A second aspect of the present invention is a method for producing a titanium ingot by a continuous casting process, which comprises pouring a molten titanium material into a coolable mold having upper and lower openings, heating the surface of the molten titanium material in the mold, and cooling and solidifying the material through the mold while pulling out the solidified material downward using a jig; a step of heating the titanium ingot to a temperature of 750° C. or higher and lower than the β transformation point, and rolling the titanium ingot to a rolling reduction of 90% or higher to produce a rolled plate; A process of heat treating at a temperature of 600°C or more and 750°C or less for a time of 20 minutes or more and 120 minutes or less, cooling from the heat treatment temperature to 500°C at an average cooling rate of 20°C / min or more, and cooling from the heat treatment temperature to a temperature of 300°C or less at an average cooling rate of 10°C / min or less. the titanium material has a chemical composition including, by mass%, Sn: 0% or more and 2.0% or less, Zr: 0% or more and 5.0% or less, Al: 0% or more and 7.0% or less, N: 0% or more and 0.100% or less, C: 0% or more and 0.080% or less, H: 0% or more and 0.0150% or less, O: 0% or more and 1.000% or less, Fe: 0% or more and 0.500% or less, Cr: 0% or more and 0.500% or less, Ni: 0% or more and 0.090% or less, Cu: 0% or more and 1.5% or less, and Mo: 0% or more and 0.750% or less, with the balance being Ti and impurities, and the total content of Fe, Cr, and Ni is 0% or more and 0.500% or less; This is a method for manufacturing titanium material for manufacturing metal foil. (8) The method for producing a titanium material for producing a metal foil according to the above (7) includes a step of hot working the titanium ingot to produce a slab, In the step of producing the rolled plate, the slab may be rolled instead of the titanium ingot. (9) In the method for producing a titanium material for producing a metal foil according to the above (7) or (8), the casting means is an electron beam melting method, The amount of electron beam irradiation into the internal space of the mold in the electron beam melting method is 150 W / cm 2 and the melting rate of the titanium material is 2.5 ton / h or less, and the material may be melted by irradiating the electron beam. (10) The method for producing titanium material for producing metal foil described in (9) above is characterized in that X in the unit of cm is the ratio of the horizontal cross-sectional area of ​​the internal space of the mold to the circumferential length of the inner circumference in the horizontal cross section of the mold, and W / cm is the dose of the electron beam in the electron beam melting method. 2 The Y in the formula (2) is Y=-3.8X+(135±25)...Equation (2) may satisfy the relationship: (11) In the method for producing a titanium material for producing a metal foil according to the above (7) or (8), the casting means is a plasma melting method, The plasma irradiation dose into the mold in the plasma melting method was 380 W / cm 2 and the melting rate of the titanium material is 2.5 ton / h or less, and the material may be melted by irradiating the plasma to the material. (12) The method for producing a titanium material for producing a metal foil according to any one of (7) to (11) above is characterized in that the horizontal cross section of the space inside the mold is 2The ratio of the area to the circumference in cm may be between 7.5 cm and 22.5 cm.

[0015] (13) A third aspect of the present invention is a titanium material for producing metal foil according to the above (6), which is attached along the outer circumferential surface of a cylindrical inner drum; and a welded portion disposed at the butt joint of the titanium material. Effect of the Invention

[0016] As described above, according to the above aspects of the present invention, it is possible to suppress the occurrence of macroscopic patterns when the titanium material for use in producing metal foil is used for a drum for producing metal foil. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 is a schematic diagram for explaining a method for inspecting a titanium material for manufacturing metal foil or a metal foil manufacturing drum according to one embodiment of the present invention. [Diagram 2] This is a schematic diagram of the surface of a titanium material for metal foil production, showing an example of the arrangement of a current-carrying electrode probe and a potential detection probe in an inspection method for a titanium material for metal foil production or a metal foil production drum according to one embodiment of the present invention. [Diagram 3] 1 is a photomicrograph showing an example of a macroscopic pattern observed on the surface of a titanium material after corrosion. [Figure 4] FIG. 1 is a micrograph showing an example of a macroscopic pattern observed on the surface of a titanium plate after corrosion, and is a reference diagram in which the macroscopic pattern is emphasized to show its location. [Diagram 5] FIG. 1 is a schematic diagram of a copper foil manufacturing apparatus showing one embodiment of a use of a metal foil manufacturing drum. [Figure 6] FIG. 1 is a schematic diagram showing a metal foil manufacturing drum according to an embodiment of the present invention. [Figure 7] FIG. 2 is a cross-sectional view showing an example of a horizontal section of a mold used in an electron beam melting method or a plasma arc melting method. [Figure 8]FIG. 2 is a cross-sectional view showing another example of a horizontal section of a mold used in an electron beam melting method or a plasma arc melting method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Preferred embodiments of the present invention will now be described in detail. <Background> First, before describing the titanium material for metal foil manufacturing according to the present embodiment, the background of the inventors' focus on the voltage on the surface of the titanium material for metal foil manufacturing will be described. In order to manufacture a metal foil, such as a copper foil, with high precision and uniform thickness using a metal foil manufacturing drum made of titanium, it is important to homogenize the chemical composition and metal structure of the titanium material constituting the metal foil manufacturing drum to prevent macroscopic patterns on the titanium material surface, and to achieve uniform corrosion of the drum to reduce macroscopic patterns caused by non-uniform macroscopic structures. The inventors have found that by homogenizing the conductivity of the titanium material surface, macroscopic patterns can be significantly suppressed, and the occurrence of macroscopic patterns due to non-uniform corrosion of the titanium material surface during the copper foil manufacturing process can be significantly suppressed.

[0019] Factors that vary the electrical conductivity of the surface of titanium material for metal foil production include inhomogeneity of the chemical composition, strain, crystal structure, crystal orientation distribution, and other inhomogeneity of the metal structure. Therefore, the electrical resistivity of the surface of titanium material for metal foil production can comprehensively indicate various internal quality factors resulting from the metal structure, such as the chemical composition, crystal structure, crystal orientation, defects, segregation, processing strain, and residual strain.

[0020] For example, regarding the chemical composition, it is estimated that the electrical resistivity (μΩ·cm) of the surface of titanium material for metal foil production has a positive linear correlation with the total concentration of O, N, and C, the total concentration of Fe, Cr, Ni, and Mo, and the hydrogen concentration. Areas where these elements are segregated have higher electrical resistivity than areas where they are not segregated. The inventors have found that, among internal quality factors, segregation in particular affects the electrical resistivity of the surface of titanium material for metal foil production.

[0021] For example, with regard to the metal structure, the electrical resistivity (μΩ·cm) of the surface of titanium material for metal foil production is presumed to have a positive linear correlation with the amount of strain. Also, the electrical resistivity (μΩ·cm) of the surface of titanium material for metal foil production is presumed to have a negative linear correlation with the angle between the current direction and the c-axis of the α-phase crystal structure. Furthermore, the electrical resistivity (μΩ·cm) of the surface of titanium material for metal foil production is presumed to be proportional to the reciprocal of the crystal grain size in the metal structure (inversely proportional to the crystal grain size). Naturally, the electrical resistivity (μΩ·cm) of the surface of titanium material for metal foil production is also correlated with the surface temperature of titanium material for metal foil production.

[0022] From these findings, it was inferred that the electrical resistivity (μΩ·cm) of the surface of titanium material for metal foil production is correlated with the main internal quality factors that produce patterns such as macroscopic patterns. Therefore, by understanding the electrical resistance at each part of the surface of titanium material for metal foil production, it is possible to understand the variation in internal quality factors at each part of the surface of titanium material for metal foil production. The above is the background to the inventors' focus on the voltage on the surface of titanium material for producing metal foil.

[0023] <Titanium material for manufacturing metal foil> Based on the above findings, the inventors have invented a titanium material for producing metal foil that can suppress the occurrence of macroscopic patterns when used in a metal foil production drum. When a pair of current-carrying electrode probes are brought into contact with the surface of the titanium material for producing metal foil according to this embodiment, and a constant current is supplied, and a pair of potential-detecting probes are brought into contact with the surface at a constant probe spacing to measure the voltages at multiple points on the surface, the voltage ratio between two adjacent points among the multiple points is 0.95 or more and 1.05 or less. In such a titanium material, segregation is particularly suppressed, and the occurrence of macroscopic patterns is suppressed. The titanium material for producing metal foil according to this embodiment will be described in detail below.

[0024] (Voltage ratio) In the titanium material for manufacturing metal foil according to the present embodiment, the voltage ratio between two adjacent locations among the multiple locations on the surface is 0.95 or more and 1.05 or less. When the voltage ratio between two adjacent locations among the multiple locations is 0.95 or more and 1.05 or less, the two adjacent locations are homogeneous. As a result, no macro pattern exists at the adjacent locations, and the occurrence of a macro pattern is suppressed even during the manufacturing of the metal foil. On the other hand, when the voltage ratio between two adjacent locations among the multiple locations is less than 0.95 or more than 1.05, the two locations are heterogeneous from each other, and a macro pattern exists on the surface of the titanium material. In addition, when the voltage ratio between two adjacent locations among the multiple locations is less than 0.95 or more than 1.05, the heterogeneity causes variation in conductivity, and during the manufacturing process of the metal foil, a difference in corrosion rate occurs between the heterogeneous part and the other parts during the manufacturing of the metal foil, and a macro pattern occurs.

[0025] In the titanium material for producing metal foil according to this embodiment, preferably 95% or more of the voltage ratios between two adjacent locations among the multiple locations are 0.95 to 1.05, and more preferably 98% or more are 0.95 to 1.05. This makes the titanium material for producing metal foil homogenous over a wide range, and further suppresses the macroscopic pattern.

[0026] More preferably, in the titanium material for metal foil production according to this embodiment, the voltage ratios of any two adjacent locations among the multiple locations are all 0.95 or more and 1.05 or less. When the voltage ratios of any two adjacent locations are all 0.95 or more and 1.05 or less, the titanium material for metal foil production is free of macropatterns in any location, and even when metal foil is produced using the titanium material for metal foil production, the occurrence of macropatterns is suppressed over a wide area of ​​the surface of the titanium material for metal foil production.

[0027] Here, a method for measuring voltage at each site on a titanium material for metal foil production according to this embodiment will be described with reference to Figures 1 and 2. Figure 1 is a schematic diagram for explaining a method for inspecting a titanium material for metal foil production or a metal foil production drum according to one embodiment of the present invention. Figure 2 is a schematic diagram of the surface of a titanium material for metal foil production showing an example of the arrangement of a current-carrying electrode probe and a potential detection probe in the method for inspecting a titanium material for metal foil production or a metal foil production drum according to this embodiment.

[0028] First, as shown in Fig. 1, a pair of current-carrying electrode probes 20A, 20B are brought into contact with a surface 11 of a titanium material 10 for producing metal foil, and a constant current I is supplied to the surface 11. As a result, the constant current I flows between a-a' where the current-carrying electrode probes 20A, 20B are in contact with each other, and a predetermined potential difference is generated.

[0029] Next, a pair of potential detection probes 30A, 30B are brought into contact with the plurality of points on the surface 11 to which the constant current I is supplied, with the probe distance L therebetween, to measure a plurality of voltages V1 to V n The pair of potential detection probes 30A and 30B repeatedly contacts the surface 11 to detect a plurality of voltages V1 to V n Alternatively, multiple pairs may be simultaneously in contact with the surface 11 to detect multiple voltages V1 to V n may be detected.

[0030] Here, the probe interval L is not particularly limited, but is determined, for example, according to the size of the macro pattern. From the experience of the present inventors, the macro pattern is about 2 to 3 mm. The present inventors have found that when the probe interval L is 3% or more of the macro pattern, the voltage difference from other parts can be detected sufficiently significantly. on the other hand The probe interval L is, for example, 67 mm or less, and preferably 33 mm or less.

[0031] Furthermore, the probe interval L is determined, for example, according to the average crystal grain size of the titanium material 10 for producing metal foil. That is, the electrical resistance of the surface 11 of the titanium material 10 for producing metal foil is also affected by the number of crystal grain boundaries of the titanium material 10 for producing metal foil at the measurement site. Therefore, from the viewpoint of leveling out the effect of crystal grain boundaries on the electrical resistance, it is preferable that a sufficient number of crystal grain boundaries are included on the surface 11 within the probe interval L.

[0032] For example, when the crystal grain size observed on surface 11 is in the range of 20 to 40 μm, there will be about 50 to 100 crystal grain boundaries in a 2 mm macro pattern. In order to fully separate the effect of the macro pattern on the electrical resistance from the effect of the number of crystal grain boundaries, it is preferable that at least about 125 crystal grain boundaries are present on surface 11 within the probe interval L. From this viewpoint, the probe interval L is, for example, 125 times or more, preferably 140 times or more, the average crystal grain size.

[0033] As described above, the probe interval L between bi-bi' (i is an integer selected from 1 to n) where the potential detection probes 30A, 30B are in contact can be determined according to the average crystal grain size and / or the size of the macro pattern of the titanium material 10 for producing metal foil. When the average crystal grain size and the size of the macro pattern are simultaneously considered, the probe interval L is, for example, 125 times or more the average crystal grain size and 67 mm or less, and preferably 140 times or more the average crystal grain size and 33 mm or less.

[0034] The electrical resistance at each site on the surface of the titanium material for producing metal foil corresponds to the voltage at that site when a constant current I is supplied. Therefore, by measuring the voltages V1 to Vn at sites b1-b1' to bn-bn' between a-a' where the current-carrying electrode probes 20A, 20B on the surface 11 are in contact, and comparing these, it is possible to grasp the variation in internal quality factors at each site on the surface of the titanium material for producing metal foil. n By comparing the results, it is possible to assess the uniformity of corrosion and the quality of the metal foil production drum.

[0035] For example, in FIG. 1, when an inhomogeneous portion 12 such as a macro pattern is present in the portion bn-bn′, the voltage V n A voltage value different from that at other portions is detected at bn-bn', and it can be determined that a heterogeneous portion 12 exists at the portion bn-bn'.

[0036] Also, the voltage V i The arrangement of the parts bi-bi' (i is an integer selected from 1 to n) for measuring is such that, between a-a', the part bi-bi' of a measurement target is arranged along the sheet width direction of the titanium material for producing metal foil on a straight line L1 connecting the parts bm-bm' (m is an integer selected from 1 to n) of another measurement target, as shown in Figure 2.

[0037] After the voltage is detected at the portion bi-bi', the pair of current-carrying electrode probes 20A, 20B are shifted from the line L1 in a direction perpendicular to the sheet width direction and brought into contact with the line L1. At the position shifted from the line L1, the voltages V1' to V2 at the portions c1-c1' to cn-cn' arranged on the line L2 parallel to the line L1 are measured. n The distance between the straight lines L1 and L2 is not particularly limited, but is preferably set to be equal to the size of the macro pattern or defect in question, for example.

[0038] By appropriately repeating the above, a plurality of voltages V1 to V2 are applied to a plurality of points on the surface 11 to which the constant current I is supplied. n Detect.

[0039] Next, the ratio of the voltages at two adjacent points among the multiple points is calculated. Specifically, for example, in FIG. 2, the voltage V i is the voltage V of the adjacent part b(i-1)-b(i-1)' i-1 and the voltage V at the part b(i+1)-b(i+1)' i+1 are compared with V i / V i-1 and V i+1 / V i (or V i-1 / V iand V i / V i+1 So far, we have explained the method for calculating the voltage ratio between two adjacent points on the surface of a titanium material for manufacturing metal foil.

[0040] (chemical composition) The titanium material for producing metal foil according to this embodiment has a chemical composition containing, by mass%, Sn: 0% or more and 2.0% or less, Zr: 0% or more and 5.0% or less, Al: 0% or more and 7.0% or less, N: 0% or more and 0.100% or less, C: 0% or more and 0.080% or less, H: 0% or more and 0.0150% or less, O: 0% or more and 1.000% or less, Fe: 0% or more and 0.500% or less, Cr: 0% or more and 0.500% or less, Ni: 0% or more and 0.090% or less, Cu: 0% or more and 1.5% or less, and Mo: 0% or more and 0.750% or less, with the balance containing Ti and impurities, and the total content of Fe, Cr, and Ni is 0% or more and 0.500% or less.

[0041] The titanium material for manufacturing metal foil according to this embodiment may contain Fe, Cr, or Ni. Since Fe, Cr, and Ni are β-phase stabilizing elements, when Fe, Cr, and Ni are contained, β-phase is easily formed. Since the β-phase corrodes preferentially to the α-phase, when a titanium drum having a titanium material containing the β-phase on its surface is used for manufacturing metal foil, the β-phase corrodes preferentially and a macro pattern is formed on the drum surface. As a result, the macro pattern may be transferred to the metal foil. Therefore, it is preferable that Fe, Cr, and Ni are small, and for example, the total content of Fe, Cr, and Ni is preferably 0% by mass or more and 0.500% by mass or less.

[0042] It is known that Fe, Cr, and Ni form compounds with Ti when their concentrations are high. Fe, Cr, and Ni form, for example, TiFe, TiCr2, and Ti2Ni together with Ti. Among these, Ni is more likely to form compounds with Ti than Fe and Cr. Therefore, in the temperature range in which Ni and Ti can diffuse during hot rolling and annealing, the precursor stage, which is the stage before Ti2Ni is formed, occurs early, and a micro-region in which Ni is concentrated is formed. When a micro-region in which Ni is concentrated is formed, the hardness of the titanium material surface varies, and polishing unevenness is likely to occur. As a result, macroscopic patterns are likely to occur. In order to suppress such Ni concentration, the Ni content is, for example, 0% by mass or more and 0.090% by mass or less. The Ni content is preferably 0.012% by mass or more. This is because, as a unique phenomenon, when a trace amount of Ni is contained, there is a behavior that makes it easy to recrystallize, and during heating in the rolling process or heat treatment process, a uniform metal structure throughout the thickness, such as an equiaxed structure or a recrystallized structure, is easily obtained. The Ni content is preferably 0.070 mass % or less.

[0043] Cu also combines with Ti to form Ti2Cu. Cu combines with Ti with the same ease as Fe and Cr.

[0044] The Fe content is, for example, 0.02% by mass or more and 0.500% by mass or less. As described above, it is preferable that Fe, Cr and Ni are small, but the Fe content may be, for example, 0.040% by mass or more.

[0045] In addition, Fe, Cr, and Ni are elements that are distributed in greater amounts to the liquid phase than to the solid phase during the solidification process of titanium. Therefore, these elements are prone to segregation in titanium materials. If these elements segregate and the chemical composition becomes inhomogeneous, the surface condition of the titanium material will become inhomogeneous.

[0046] In order to reduce the above-mentioned inhomogeneity of the chemical components, the titanium material for manufacturing metal foil according to this embodiment preferably contains Mo. Mo is a β-phase stabilizing element like Fe, Cr, and Ni, but unlike these elements, it is an element that distributes more to the solid phase than to the liquid phase during the solidification process of titanium. By containing Mo, the chemical components in the titanium material are homogenized, and the conductivity of the titanium material surface is made uniform. As a result, the surface condition of the titanium material becomes homogenous, and the occurrence of macroscopic patterns is further suppressed.

[0047] The content of Mo is preferably 0.5 to 1.2 times the total content of Fe, Cr, and Ni in mass%. When the content of Mo is 0.5 to 1.2 times the total content of Fe, Cr, and Ni in mass%, the chemical components are homogenized, the surface state is homogenized, and the occurrence of macroscopic patterns is suppressed. When the content of Mo is 0.5 to 1.2 times the total content of Fe, Cr, and Ni in mass%, the formation of the β phase is suppressed to such an extent that the influence of the difference in corrosion rate between the α phase and the β phase is not manifested. As a result, the etching behavior of titanium and the electrodeposition state of copper in the electrolytic solution for manufacturing the metal foil can be made more stable. The content of Mo is more preferably 0.7 times or more the total content of Fe, Cr, and Ni in mass%. Moreover, the content of Mo is more preferably 1.0 times or less the total content of Fe, Cr, and Ni in mass%.

[0048] For example, when the titanium material contains 0.0300% Fe by mass, 0.010% Cr by mass, and 0.020% Ni by mass, the total content of Fe, Cr, and Ni is 0.060% by mass. Therefore, in this case, the Mo content is preferably 0.030% by mass or more and 0.072% by mass or less. Since Mo is not necessarily contained, the lower limit of the Mo content is 0% by mass.

[0049] The titanium material for producing a metal foil according to this embodiment may contain O, N, C, and H.

[0050] O contributes to improving the strength of the titanium material and increasing the surface hardness. However, if the strength of the titanium material becomes too high, it becomes difficult to polish the titanium material when it is made into a drum. Therefore, when O is contained in the titanium material for manufacturing metal foil, the O content is preferably 1.000 mass% or less. The O content is more preferably 0.120 mass% or less, even more preferably 0.065 mass% or less, and even more preferably 0.055 mass% or less.

[0051] N has a smaller solid solubility limit in α-Ti than O, and therefore tends to form nitrides with Ti. If nitrides are formed, unevenness due to polishing or unevenness due to corrosion during use may occur on the drum surface. Therefore, it is preferable to suppress the content of N as much as possible. The content of N can be, for example, 0.100% by mass or less, and more preferably 0.020% by mass or less.

[0052] C also has a smaller solid solubility limit in α-Ti than O, and therefore tends to form carbides together with Ti. When carbides are formed, the drum surface may become uneven due to polishing or uneven due to corrosion during use, as with nitrides. Therefore, it is preferable to suppress the C content as much as possible. The C content can be, for example, 0.080 mass% or less, and more preferably 0.020 mass% or less.

[0053] H forms hydrides together with Ti. When hydrides are formed, the titanium material may become embrittled. Furthermore, the hydrides may cause macroscopic patterns. Therefore, it is preferable to suppress the content of H as much as possible. The content of H is more preferably 0.013 mass% or less.

[0054] Like Mo, O, N, and C are elements that are distributed in greater amounts to the solid phase than to the liquid phase during the solidification process of titanium. Therefore, the above-mentioned Mo content may be determined taking into account the O, N, and C contents.

[0055] The titanium material for producing a metal foil according to this embodiment may contain at least one of Cu, Sn, Zr, and Al.

[0056] The balance of the chemical composition of the titanium material for manufacturing metal foil according to this embodiment may be Ti and impurities. Specific examples of impurities include Cl, Na, Mg, Si, and Ca mixed in during the refining process, and Nb, Ta, V, and the like mixed in from scrap. The total amount of impurities is at a level that does not cause problems if it is 0.5 mass% or less.

[0057] In this embodiment, as described above, V is contained as an impurity. V is an element that retards recrystallization. If V is contained in excess, it becomes difficult to obtain a uniform metal structure throughout the thickness, for example, an equiaxed structure or a recrystallized structure, during heating in the rolling process or during the heat treatment process. Therefore, V is not added in this embodiment.

[0058] More specifically, taking into consideration impurities that may be contained, the titanium material for manufacturing metal foil according to this embodiment is, for example, In mass%, N: 0% or more and 0.100% or less, C: 0% or more and 0.080% or less, H: 0% or more and 0.0150% or less, O: 0% or more and 0.400% or less may be contained.

[0059] In addition, the titanium material for manufacturing metal foil according to this embodiment is, for example, Contains Fe, Cr, Ni, and Mo; The Ni content is 0 mass% or more and 0.090 mass% or less, On a mass basis, the content of Mo is 0.5 to 1.2 times the total content of Fe, Cr, and Ni.

[0060] In addition, the titanium material for manufacturing metal foil according to this embodiment is, for example, In mass%, N: 0% or more and 0.100% or less, C: 0% or more and 0.080% or less, H: 0% or more and 0.0150% or less, O: 0% or more and 0.400% or less, Fe: 0.02% or more and 0.500% or less, Ni: 0% or more and 0.090% or less, and Cu: 0% or more and 1.5% or less; The balance may contain Ti and impurities.

[0061] In addition, the titanium material for manufacturing metal foil according to this embodiment is, for example, In mass%, Sn: 0.2% or more and 2.0% or less, Zr: 0.2% or more and 5.0% or less, and Al: 0.2% or more and 3.0% or less, one or more of the group consisting of, is contained in a total amount of 0.2% or more and 5.0% or less, N: 0% or more and 0.100% or less, C: 0% or more and 0.080% or less, H: 0% or more and 0.0150% or less, O: 0% or more and 1.000% or less, and Fe: 0% or more and 0.500% or less; The balance may contain Ti and impurities.

[0062] In addition, the titanium material for manufacturing metal foil according to this embodiment is, for example, Contains more than 1.8 mass% and not more than 7.0 mass% Al, with the balance containing Ti and impurities; When the Al content is [Al%], the Zr content is [Zr%], the Sn content is [Sn%], and the O content is [O%] in mass%, the following formula (1) is satisfied: Aleq=[Al%]+[Zr%] / 6+[Sn%] / 3+10×[O%] The Al equivalent Aleq represented by formula (1) is 7.0 mass% or less.

[0063] The lower limit of the content of each of the elements described above is 0 mass %, and it goes without saying that the titanium material for producing a metal foil according to this embodiment does not necessarily need to contain each of the elements described above. The chemical composition of the titanium material for producing metal foil according to this embodiment has been described above.

[0064] In the titanium material for producing metal foil according to the present embodiment described above, the voltage ratio between two adjacent points among the multiple points on the surface is 0.95 to 1.05, so the influence of the chemical composition between adjacent points is uniform. As a result, no macroscopic pattern exists between the adjacent points, and the occurrence of the macroscopic pattern is suppressed even during the production of metal foil.

[0065] The macro pattern can be observed by polishing the surface of the titanium plate with #800 emery paper and corroding the surface with a solution of 10% by mass of nitric acid and 5% by mass of hydrofluoric acid. As an example, photographs of the surface of titanium material on which a macro pattern has been generated are shown in Figures 3 and 4. Note that Figures 3 and 4 are photographs of different titanium plates. The "macro pattern" refers to a portion where a stripe of a different color has been generated along the rolling direction and is several millimeters long. For example, in Figure 4, a macro pattern of the shape shown in Figure 4(B) has been generated at the location indicated by the arrow in Figure 4(A). If such a macro pattern is generated in titanium material, the macro pattern will be transferred to the metal foil that is finally manufactured.

[0066] As described above, the titanium material for metal foil production according to this embodiment is suitable as a material for a drum for metal foil production because it can sufficiently suppress the occurrence of macroscopic patterns when used in the drum for metal foil production. Therefore, in one aspect, the present invention also relates to a metal foil production drum manufactured using the titanium material for metal foil production according to the present invention. Such a metal foil production drum suppresses the occurrence of macroscopic patterns and can produce high-quality copper foil.

[0067] A metal foil manufacturing drum manufactured using the titanium material for manufacturing metal foil according to the present invention will be described with reference to Figs. 5 and 6. Fig. 5 is a schematic diagram of a copper foil manufacturing apparatus showing one embodiment of the use of the metal foil manufacturing drum, and Fig. 6 is a schematic diagram showing a metal foil manufacturing drum according to one embodiment of the present invention. The copper foil manufacturing apparatus 100 includes, for example, an electrolytic cell 110 in which a copper sulfate solution is stored, an electrodeposition drum 120 provided in the electrolytic cell 110 so as to be partially immersed in the copper sulfate solution, and an electrode plate 130 provided in the electrolytic cell 110 so as to be immersed in the copper sulfate solution and to face the outer circumferential surface of the electrodeposition drum 120 at a predetermined interval, as shown in Fig. 5. By applying a voltage between the electrodeposition drum 120 and the electrode plate 130, copper foil F is electrodeposited on the outer circumferential surface of the electrodeposition drum 120. The copper foil F having a predetermined thickness is peeled off from the metal foil manufacturing drum 120 by the winding section 140 and wound around the winding roll 160 while being guided by the guide roll 150.

[0068] The electrodeposition drum 120 includes a cylindrical inner drum 121, a titanium material 122 for producing metal foil according to the present embodiment that is attached along the outer circumferential surface of the inner drum 121, a welded portion 123 arranged at the butt joint of the titanium material 122 for producing metal foil, a side plate 124 provided on the side of the inner drum, and a rotating shaft 125. The metal foil producing drum according to the present embodiment is a part of the electrodeposition drum 120, and is composed of the titanium material 122 for producing metal foil according to the present embodiment that is attached along the outer circumferential surface of the cylindrical inner drum 121, and the welded portion 123 arranged at the butt joint of the titanium material 122 for producing metal foil. The side plate 124 is attached to both ends in the axial direction of the inner drum 121 and the titanium material 122 for producing metal foil. The rotating shaft 125 is provided on the side plate 124 coaxially with the central axis A of the inner drum 121.

[0069] The metal foil production drum of this embodiment can be manufactured by known methods, for example, by stretching the titanium sheet material for metal foil production of this embodiment over the outer surface of an inner drum and welding the two butted ends of the titanium sheet material for metal foil production that has been processed into a cylindrical shape.

[0070] The size of the metal foil manufacturing drum according to this embodiment is not particularly limited, but for example, the diameter may be 1 m or more, 2 m or more, or 5 m or less.

[0071] Such a metal foil producing drum suppresses the occurrence of macroscopic patterns and can produce high quality copper foil.

[0072] The titanium material for use in producing metal foil according to the embodiment described above may be produced by any method. For example, it can be produced by the method for producing titanium material for use in producing metal foil according to the embodiment described below.

[0073] <Method of manufacturing titanium material for metal foil production> Next, a method for producing a titanium material for manufacturing metal foil according to this embodiment will be described. The method for producing a titanium material for manufacturing metal foil according to this embodiment includes the steps of injecting molten titanium into a mold that is open at the top and bottom and can be cooled, and heating the surface of the molten titanium in the mold, and cooling and solidifying the titanium through the mold while pulling the solidified titanium downward using a jig to produce a titanium ingot by continuous casting, heating to a temperature of 750°C or higher and lower than the β transformation point, and rolling to a rolling reduction of 90% or more to produce a rolled plate, and heat treating at a temperature of 600°C or higher and 750°C or lower for a time of 20 minutes to 120 minutes, cooling from the heat treatment temperature to 500°C at an average cooling rate of 20°C / min or higher, and cooling from the heat treatment temperature to a temperature of 300°C or lower at an average cooling rate of 10°C / min or lower.

[0074] (Titanium ingot manufacturing process) First, titanium having the above-mentioned chemical composition is melted by electron beam remelting (EBR) or plasma arc melting (PAM) to produce a titanium ingot. In EBR, an electron beam is irradiated from an electron beam gun, and in PAM, a plasma arc is irradiated from a plasma torch to melt raw materials including titanium. Compared with vacuum arc remelting (VAR), which melts an electrode by an arc between a titanium consumable electrode and molten titanium in a water-cooled copper mold, EBR and PAM have a relatively shallow molten pool, which is the part where the molten titanium exists in the mold, and a fast solidification rate, so that solidification segregation of Fe, Cr, Ni, O, etc. can be reduced. By using a titanium ingot with suppressed solidification segregation, the titanium material for metal foil production produced is homogenized. As a result, the surface condition of the titanium material becomes homogenous and the occurrence of macroscopic patterns is suppressed.

[0075] For melting titanium, in order to stabilize the depth and shape of the molten pool, it is more preferable to use the electron beam melting (EBR) method, which allows for fast and easy irradiation scanning of the energy source to achieve a uniform and stable heat input distribution to the titanium molten surface in the mold. Hereinafter, the electron beam melting method (EBR) and the plasma amplifying method (PAM) used in the method for producing a titanium material for producing a metal foil according to this embodiment will be described in detail.

[0076] [Electron Beam Melting (EBR)] Electron beam melting is a method of melting metals such as titanium with an electron beam emitted from an electron gun in a vacuum, pouring the molten metal into a mold such as a water-cooled copper mold, and solidifying it to produce an ingot. Generally, a bottomless mold is used to continuously cast the ingot while pulling it out. During this process, the molten metal surface in the mold is heated by irradiating it with an electron beam, and the molten metal surface in the mold is maintained.

[0077] In order to stabilize the depth and shape of the molten pool and maintain the molten surface, the value obtained by dividing the electron beam irradiation output into the mold by the mold inner area, that is, the irradiation amount per unit area, is set to 150 W / cm 2 It is preferable to melt titanium under conditions of a temperature of 0.5 to 2.0 t / h or less and a melting rate of 2.5 ton / h or less. The melting rate is more preferably 0.5 to 2.0 t / h.

[0078] [Plasma Melting Method (PAM)] The plasma melting method is a method of producing an ingot by melting a metal such as titanium with a plasma arc emitted from a plasma torch in an inert gas atmosphere such as an argon atmosphere, pouring the molten metal into a mold such as a water-cooled copper mold, and solidifying it. Generally, a bottomless mold is used to continuously cast the ingot while pulling it out. During this process, the molten metal surface in the mold is heated by irradiating it with a plasma arc, and the molten metal surface in the mold is maintained.

[0079] In order to stabilize the depth and shape of the molten pool and maintain the molten surface, the plasma irradiation power into the mold divided by the mold area, that is, the irradiation amount per unit area, is set to 380 W / cm 2 It is preferable to melt titanium under conditions of a temperature of 0.5 to 2.0 t / h or less and a melting rate of 2.5 ton / h or less. The melting rate is more preferably 0.5 to 2.0 t / h.

[0080] Examples of horizontal cross sections of a mold 40 used for EBR or PAM are shown in Figures 7 and 8. A circular mold 40A as shown in Figure 7 and a rectangular mold 40B as shown in Figure 8 are typical examples of horizontal cross sections of molds used for EBR or PAM. In these horizontal cross sections, the internal space 41A of mold 40A and the internal space 41B of mold 40B are each measured in cm 2The ratio of the area to the perimeter in cm, that is, the area / perimeter, is preferably 7.5 cm or more and 22.5 cm or less. This increases the cooling rate of the molten titanium by the mold, making it possible to further suppress solidification segregation. The area / perimeter is more preferably 15.0 cm or less, and even more preferably 11.0 cm or less, and a mold with such an area / perimeter can significantly suppress solidification segregation. From the viewpoint of productivity, the area / perimeter is preferably substantially 7.5 cm or more. In addition, when the horizontal cross section is, for example, a rectangular shape, the four corners C are often chamfered to form a polygon, so the above-mentioned area and perimeter are obtained taking into account the shape shown in FIG. 8. In addition, the thickness of the mold is not particularly limited, but may be, for example, less than 300 mm.

[0081] As mentioned above, EBR is suitable for maintaining a stable molten metal surface and molten metal pool shape in the mold because the irradiation position of the electron beam can be easily moved. Therefore, by using electron beam melting and setting the irradiation amount per unit area (Y) in the electron beam irradiation output into the mold according to the area / perimeter (X), the molten metal surface and molten metal pool shape in the mold can be maintained more stably. Y=-3.8X+(135±25)...Equation (2)

[0082] (Slab manufacturing process) The method for producing titanium material for metal foil according to the present embodiment includes a slab production step in which a titanium ingot is hot worked to produce a slab, and in the step of producing a rolled plate, the slab is preferably rolled instead of the titanium ingot. For example, if necessary, the titanium ingot may be hot forged or bloomed by a known method before rolling to produce a slab from the titanium ingot. This step is also performed in the case of a cylindrical ingot or in the case of a rectangular ingot where the thickness or width needs to be adjusted. By using the slab, the rolling step can be performed more uniformly, and the metal structure can be made even more uniform.

[0083] (Rolling process) Next, the produced titanium ingot is directly rolled, or a slab that has been hot worked into a rolling shape as necessary is rolled to produce a rolled plate. In this process, the material to be rolled is heated to a temperature of 750°C or higher and lower than the β transformation point, and rolled to a rolling reduction of 90% or more. The heating temperature and rolling reduction are explained below.

[0084] The heating temperature in this step is 750°C or higher and lower than the β transformation point. By heating to a temperature of 750°C or higher and lower than the β transformation point, the metal structure can be sufficiently equiaxed, and the occurrence of macroscopic patterns in the rolled plate can be prevented. The rolling temperature is preferably 200°C or higher. In addition, the rolling temperature is preferably (β transformation point - 50)°C or lower.

[0085] The reduction rate in this process is 90% or more. By setting the reduction rate at 90% or more, it is possible to sufficiently refine the coarse grains, and also to make the metal structure of the rolled plate equiaxed, thereby preventing the occurrence of macroscopic patterns. The higher the reduction rate in this process, the better the structure, so it is sufficient to determine it according to the required product size and the characteristics of the manufacturing mill.

[0086] Furthermore, by heating the titanium ingot to a temperature of 750° C. or higher and lower than the β transformation point, and rolling it to a rolling reduction of 90% or higher, recrystallization nuclei can be introduced homogeneously and sufficiently throughout the rolled sheet.

[0087] Here, in this embodiment, the "β transformation point" means the boundary temperature at which the α phase begins to form when the titanium alloy is cooled from the β single-phase region. The β transformation point can be obtained from a phase diagram. The phase diagram can be obtained, for example, by the CALPHAD (Computer Coupling of Phase Diagrams and Thermochemistry) method. Specifically, the phase diagram of the titanium alloy can be obtained by the CALPHAD method using Thermo-Calc, an integrated thermodynamic calculation system from Thermo-Calc Software AB, and a predetermined database (TI3), and the β transformation point can be calculated.

[0088] (Heat treatment process) Next, the rolled plate is heat-treated at a temperature of 600°C to 750°C for 20 minutes to 120 minutes, cooled from the heat treatment temperature to 500°C at an average cooling rate of 20°C / min or more, and cooled from the heat treatment temperature to a temperature of 300°C or less at an average cooling rate of 10°C / min or less. By heat-treating at a temperature of 600°C to 750°C for 20 minutes to 120 minutes, a homogeneous recrystallized structure can be formed throughout the rolled plate. In addition, by the average cooling rate from the heat treatment temperature to 500°C being 20°C / min or more, element distribution driven by the formation of a second phase occurring during the cooling process is reduced, and the microscopic variation in component distribution due to element distribution is suppressed. In addition, by cooling from the heat treatment temperature to a temperature of 300°C or less at a rate of 10°C / min or less, the residual strain resulting from thermal shrinkage caused by cooling can be reduced. As a result, it is possible to obtain a highly homogeneous titanium plate in which the component distribution and residual strain are homogeneous.

[0089] (Inspection process) The titanium material obtained through the heat treatment process may be inspected for surface homogeneity by the above-mentioned method.

[0090] The titanium material produced by the method for producing a titanium material for producing a metal foil according to this embodiment has a homogenized chemical composition and metal structure. As a result, the titanium material produced by the method for producing a titanium material for producing a metal foil according to this embodiment has a surface to which a constant current is supplied by contacting a pair of current-carrying electrode probes with the surface, and among the multiple voltages detected by contacting multiple points on the surface with a pair of potential detection probes at a constant probe interval, the ratio of the voltages at two adjacent points is 0.95 to 1.05. As a result, when the titanium material produced by the method for producing a titanium material for producing a metal foil according to this embodiment is used for a drum for producing a metal foil, the occurrence of a macro pattern can be suppressed. The method for manufacturing a titanium plate according to this embodiment has been described above.

[0091] As described above, the titanium material for producing metal foil according to this embodiment is shrink-fitted into the inner drum, and then the surface is polished to become the top skin of the metal foil production drum. If the load during polishing varies, the amount of strain introduced directly below the drum surface may vary. If the amount of strain varies, the electrical resistivity of the surface of the metal foil production drum may change. Therefore, the fluctuation range of the load when polishing the metal foil production drum is preferably 10% or less, more preferably 5% or less, and even more preferably 3% or less.

[0092] The metal foil produced by the metal foil production drum produced using the titanium material for producing metal foil is not particularly limited, and examples thereof include copper foil, nickel foil, aluminum foil, and iron foil.

[0093] Hereinafter, the embodiment of the present invention will be described in detail with reference to examples. Note that the examples shown below are merely examples of the present invention, and the present invention is not limited to the following examples.

[0094] [Example 1] (Titanium material manufacturing) First, a number of titanium raw materials having different chemical compositions were prepared, and the titanium raw materials were melted using the melting methods shown in Tables 1 to 6 to produce titanium ingots.

[0095] [Table 1]

[0096] [Table 2]

[0097] [Table 3]

[0098] [Table 4]

[0099] [Table 5]

[0100] [Table 6]

[0101] In the electron beam melting method, the electron beam irradiation output into the mold was adjusted according to the mold shape so that the irradiation amount per unit surface (Y) was within the range of formula (2) according to the area / perimeter (X) of the mold, with the aim being approximately the central value of formula (2). However, although there were some cases in which the electron beam irradiation output was changed from the central value of formula (2), the electron beam irradiation amount in the electron beam melting method was always 150 W / cm 2 The melting rate was set at 1.0 ton / h, aiming to keep it below 2.5 ton / h. Y=-3.8X+(135±25)...Equation (2)

[0102] In the plasma melting method, the plasma irradiation power into the mold was 380 W / cm 2 The melting rate was set at 1.0 ton / h, aiming for a rate of 2.5 ton / h or less.

[0103] In the vacuum arc melting method, a water-cooled copper mold with a diameter of 750 mm and a bottom (without an opening at the bottom) was used to melt an electrode made of titanium raw material.

[0104] The molds used for casting the molten titanium were those shown in Tables 1 to 6. The "horizontal cross-sectional shape of the internal space of the mold" shown in Tables 1 to 6 is the approximate shape of the horizontal cross section of the mold in the space inside the mold, and the "details of the cross-sectional size of the mold" show the diameter R, short side A, long side B, corner C, and their areas and perimeters of the horizontal cross section in the space inside the mold. Moreover, the "irradiation amount" in Tables 1 to 6 is the irradiation amount per unit area inside the mold when the ingot manufacturing method is EBR or PAM.

[0105] For the manufactured titanium ingot, when it was cylindrical and 750 mmφ or rectangular and 350 mm thick or more, the casting surface was trimmed by cutting or the like, and then hot forging was performed to form a 250 mm thick slab. When the ingot was rectangular and 260 mm thick or less, the casting surface was trimmed by cutting or the like without hot forging. These were heated to 800 ° C and rolled at a rolling reduction rate of 90% or more to produce rolled plates with a thickness of 8 to 15 mm. The rolled plate was then heat treated at a temperature of 700 ° C for 30 minutes, and the heat-treated rolled plate was cooled so that the average cooling rate from the heat treatment temperature to 500 ° C was 20 ° C / min and the average cooling rate from the heat treatment temperature to 300 ° C was 10 ° C / min, producing a plate-shaped titanium material. The temperature was controlled by gas flow and a heater.

[0106] (Manufacture of metal foil drums) The manufactured titanium material was made into a tubular shape, which was then shrink-fitted into a cylindrical titanium material (inner drum) and its surface was polished to manufacture an electroplated drum. The load fluctuation range during polishing was set to 10% or less.

[0107] (Analysis and Evaluation) The average chemical composition, voltage ratio, and macroscopic pattern of the titanium materials according to the examples and comparative examples were evaluated. Furthermore, the voltage ratio of the electrodeposition drums manufactured using these titanium materials was evaluated.

[0108] Regarding the average chemical composition, O and N were analyzed by the inert gas fusion method using an analyzer manufactured by Leco Japan LLC (instrument name ON736). In detail, O was analyzed by the non-dispersive infrared absorption method, and N was analyzed by the thermal conductivity method. C was analyzed by the infrared absorption method using an analyzer manufactured by Leco Japan LLC (instrument name CS444). H was analyzed by the thermal conductivity method using an analyzer manufactured by Horiba Ltd. (instrument name EMGA-800M). Fe, Ni, Cr, and Mo were analyzed by ICP optical emission spectroscopy using an analyzer manufactured by Shimadzu Corporation (instrument name ICPS8100).

[0109] The voltage ratio was calculated and evaluated by the following method. A pair of current-carrying electrode probes was brought into contact with the surface of the titanium material and a constant current was supplied. Next, the pair of potential detection probes was arranged as shown in FIG. 2 with a probe interval of 30 mm, and the voltage was measured by bringing the pair of potential detection probes into contact with the surface of the titanium material in the direction of line L1. Next, the current-carrying electrode probe was shifted by 30 mm in the direction perpendicular to line L1, and the pair of potential detection probes was brought into contact along line L2 to measure the voltage. This was repeated to measure the voltage on the surface of the titanium material, and the voltage ratio of adjacent points was calculated from the measured voltage.

[0110] The voltage ratio was evaluated as follows according to the ratio of data with a voltage ratio of less than 0.95 or more than 1.05 to the total number of calculated voltage ratio data.

[0111] Excellent (A): The percentage of data with a voltage ratio of less than 0.95 or greater than 1.05 out of the total number of calculated voltage ratio data is less than 2%. Good (B): The percentage of data with a voltage ratio of less than 0.95 or greater than 1.05 out of the total number of calculated voltage ratio data is between 2% and 5%. Acceptable (C): The percentage of data with a voltage ratio of less than 0.95 or more than 1.05 out of the total number of calculated voltage ratio data is 5% or more.

[0112] Furthermore, for the examples that were rated as excellent (A), the following evaluation was performed according to the calculated voltage ratio value.

[0113] Very good (AAA): All voltage ratios are between 0.98 and 1.02, except for voltage ratios less than 0.95 or over 1.05. Better (AA): All voltage ratios are between 0.97 and 1.03 (except for extremely good cases) except for data with a voltage ratio of less than 0.95 or more than 1.05. Good (A): Data other than voltage ratios less than 0.95 or more than 1.05 All voltage ratios are 0.95 or more and 1.05 or less (except for very good and better cases)

[0114] The surfaces of 20 titanium plates of 50 x 100 mm size according to the invention examples and comparative examples were polished with #800 emery paper and the surfaces were corroded with a solution of 10% nitric acid and 5% hydrofluoric acid to observe the macroscopic patterns. Streaky patterns that occurred with a length of 3 mm or more were regarded as macroscopic patterns, and the occurrence rate was evaluated as follows.

[0115] Excellent (A): Occurrence rate is 0.05 or less per sheet Good (B): Occurrence rate is more than 0.05 / sheet and less than 0.15 / sheet Acceptable (C): Occurrence rate is more than 0.15 pieces / sheet The evaluation results are shown in Tables 7 to 12.

[0116] [Table 7]

[0117] [Table 8]

[0118] [Table 9]

[0119] [Table 10]

[0120] [Table 11]

[0121] [Table 12]

[0122] As shown in Tables 1 to 12, when the titanium material produced using the ingot produced by melting with EBR or PAM has an area / perimeter of 22.5 cm or less, the ratio of data with a voltage ratio of less than 0.95 or more than 1.05 to the total number of calculated voltage ratio data is less than 2%, and all data other than data with a voltage ratio of less than 0.95 or more than 1.05 is 0.95 or more and 1.05 or less. Such titanium material has a suppressed macro pattern on the surface. When the area / perimeter in the horizontal cross section of the mold used in the ingot production is 15.0 cm or less, the ratio of data with a voltage ratio of less than 0.95 or more than 1.05 to the total number of calculated voltage ratio data is less than 2%, and all data other than data with a voltage ratio of less than 0.95 or more than 1.05 is 0.97 or more and 1.03 or less. Such titanium material has a further suppressed macro pattern on the surface. When the area / perimeter ratio was 11.0 cm or less, the ratio of data with a voltage ratio of less than 0.95 or more than 1.05 to the total number of calculated voltage ratio data was less than 2%, and all voltage ratios other than data with a voltage ratio of less than 0.95 or more than 1.05 were 0.98 or more and 1.02 or less. Such titanium materials had extremely suppressed macroscopic patterns on their surfaces.

[0123] In addition, when the Mo content was 0.5 to 1.2 times the total content of Fe, Cr, and Ni, the ratio of data with a voltage ratio of less than 0.95 or more than 1.05 to the total number of calculated voltage ratio data was less than 2%, and all voltage ratios other than data with a voltage ratio of less than 0.95 or more than 1.05 were 0.98 to 1.02. Such titanium material had an extremely suppressed macroscopic pattern on its surface.

[0124] In addition, the evaluation results of the voltage ratio of the manufactured metal foil production drum were equivalent to those of the titanium material, and the evaluation results of the macro-pattern of the drum surface were also identical to those of the titanium material surface. Therefore, it was found that the manufacturing process of the metal foil production drum has little effect on the internal quality factors of the titanium material for metal foil production.

[0125] [Example 2] The Al content was changed, and in the same manner as in Example 1, titanium materials were produced, metal foil production drums were produced, and analysis and evaluation were carried out.

[0126] [Table 13]

[0127] [Table 14]

[0128] [Table 15]

[0129] [Table 16]

[0130] [Table 17]

[0131] [Table 18]

[0132] [Table 19]

[0133] [Table 20]

[0134] As shown in Tables 13 to 20, when the sample contains, in mass%, one or more of the group consisting of Sn: 0.2% to 2.0%, Zr: 0.2% to 5.0%, and Al: 0.2% to 3.0%, in total 0.2% to 5.0%, N: 0% to 0.10%, C: 0% to 0.08%, H: 0% to 0.015%, O: 0% to 1.0%, and Fe: 0% to 0.500%, and the voltage ratio of two adjacent points among the multiple points is 0.95 to 1.05, the macro pattern on the surface is suppressed. In addition, when the sample contains Al more than 1.8 mass% and 7.0 mass% or less, and Aleq is 7.0 mass% or less, the macro pattern on the surface is suppressed.

[0135] Furthermore, the evaluation results of the voltage ratio of the manufactured metal foil manufacturing drum were equivalent to the evaluation results of the voltage ratio of the titanium material, and the evaluation results of the macro-pattern of the drum surface were also identical to the evaluation results of the macro-pattern of the titanium material surface.

[0136] [Example 3] For the titanium ingots shown in Tables 21 and 22, when they were rectangular and 350 mm or thicker, the casting surface was prepared by cutting or the like, and then hot forging was performed to produce slabs with a thickness of 250 mm. When the ingots were rectangular and 260 mm or thinner, the casting surface was prepared by cutting or the like without hot forging. Titanium materials were then produced under the rolling conditions, heat treatment, and cooling conditions shown in Tables 23 to 25. In addition, metal foil production drums were produced and analyzed and evaluated in the same manner as in Example 1.

[0137] The β transformation points shown in Tables 22 to 25 are values ​​calculated by obtaining phase diagrams of titanium alloys using Thermo-Calc, an integrated thermodynamic calculation system from Thermo-Calc Software AB, and a specified database (TI3) according to the CALPHAD method.

[0138] [Table 21]

[0139] [Table 22]

[0140] [Table 23]

[0141] [Table 24]

[0142] [Table 25]

[0143] As shown in Tables 21 to 25, when a titanium material was produced by heating a titanium ingot to a temperature of 750°C or more and less than the β transformation point, rolling it to a rolling reduction of 90% or more, heat treating it at a temperature of 600°C or more and 750°C or less for a time of 20 minutes to 120 minutes, cooling it from the heat treatment temperature to 500°C at an average cooling rate of 20°C / min or more, and then cooling it from the heat treatment temperature to a temperature of 300°C or less at an average cooling rate of 10°C / min or less, the titanium material had a suppressed macroscopic pattern on the surface.

[0144] Furthermore, the evaluation results of the voltage ratio of the manufactured metal foil manufacturing drum were equivalent to the evaluation results of the voltage ratio of the titanium material, and the evaluation results of the macro-pattern of the drum surface were also identical to the evaluation results of the macro-pattern of the titanium material surface.

[0145] [Example 4] Titanium ingots were produced by changing the amount of electron beam irradiation into the internal space of the mold or the amount of plasma irradiation into the mold, and the melting rate, as shown in Tables 26 and 27. The "amount of irradiation" in Tables 26 and 27 means the amount of electron beam irradiation into the internal space of the mold when the titanium ingot is produced by electron beam melting, and means the amount of plasma irradiation into the mold when the titanium ingot is produced by plasma melting.

[0146] For the manufactured titanium ingot, when it was cylindrical and 750 mmφ or rectangular and 350 mm thick or more, the casting surface was trimmed by cutting or the like, and then hot forging was performed to produce a 250 mm thick slab. When the ingot was rectangular and 260 mm thick or less, the casting surface was trimmed by cutting or the like without hot forging. These were heated to 800 ° C to produce a rolled plate with a thickness of 8 mm. Then, the rolled plate was heat treated at a temperature of 700 ° C for 30 minutes, and the heat-treated rolled plate was cooled so that the average cooling rate from the heat treatment temperature to 500 ° C was 20 ° C / min and the average cooling rate from the heat treatment temperature to 300 ° C was 10 ° C / min, and a plate-shaped titanium material was manufactured. The temperature was controlled by gas flow and a heater. The results are shown in Table 28. The average chemical compositions IG1 to IG9 of the titanium material shown in Table 28 indicate that they are the same average chemical compositions as the symbols IG1 to IG9 shown in Table 22.

[0147] [Table 26]

[0148] [Table 27]

[0149] [Table 28]

[0150] As shown in Tables 26 to 28, the irradiation dose of the electron beam to the internal space of the mold in the electron beam melting method is 150 W / cm 2When the melting rate was 2.5 ton / h or less, the evaluation results of the voltage ratio and the macro pattern were excellent, and the macro pattern was also extremely suppressed. 2 Even when the dissolution rate was 2.5 ton / h or less, the evaluation results of the voltage ratio and the macro pattern were excellent, and the macro pattern was also extremely suppressed.

[0151] Furthermore, the evaluation results of the voltage ratio of the manufactured metal foil manufacturing drum were equivalent to the evaluation results of the voltage ratio of the titanium material, and the evaluation results of the macro-pattern of the drum surface were also identical to the evaluation results of the macro-pattern of the titanium material surface.

[0152] Although the preferred embodiment of the present invention has been described in detail above, the present invention is not limited to such examples. It is clear that a person having ordinary knowledge in the technical field to which the present invention pertains can come up with various modified or amended examples within the scope of the technical ideas described in the claims, and it is understood that these also naturally belong to the technical scope of the present invention. [Explanation of symbols]

[0153] 10 Titanium material for metal foil manufacturing 11 Surface 12 Heterogeneous areas 20A, 20B current-carrying electrode probe 30A, 30B potential detection probe 40, 40A, 40B molds 41A, 41B interior space 100 Copper foil manufacturing equipment 110 Electrolytic cell 120 Electroplating drum 121 Inner drum 122 Titanium 123 Welding 124 Side Panel 125 Rotational Axis 130 Electrode plate 140 Winding section 150 Guide Roll 160 Winding roll

Claims

1. In mass percent, Sn: 0% or more and 2.0% or less, Zr: 0% or more and 5.0% or less, Al: 0% or more and 7.0% or less, N: 0% or more and 0.100% or less, C: 0% or more and 0.080% or less, H: 0% or more and 0.0150% or less, O: 0% or more and 1.000% or less, Fe: 0% or more and 0.500% or less, Cr: 0% or more and 0.500% or less, Ni: 0% or more and 0.090% or less, Cu: 0% or more and 1.5% or less, and Mo: 0% or more and 0.750% or less; The balance has a chemical composition consisting of Ti and impurities, The total content of Fe, Cr, and Ni is 0% or more and 0.500% or less, A titanium material for producing metal foil, in which when a pair of current-carrying electrode probes are brought into contact with the surface to supply a constant current, and a pair of potential-detecting probes are brought into contact with the surface at a probe spacing of 125 times or more the average crystal grain size and 67 mm or less, and voltages at multiple locations on the surface are measured, the ratio of voltages between two adjacent locations among the multiple locations is 0.95 or more and 1.05 or less.

2. In mass percent, N: 0% or more and 0.100% or less, C: 0% or more and 0.080% or less, H: 0% or more and 0.0150% or less, O: 0% or more and 0.400% or less, Fe: 0.02% or more and 0.500% or less, Ni: 0% or more and 0.090% or less, and The titanium material for manufacturing metal foil according to claim 1, containing Cu: 0% or more and 1.5% or less.

3. Contains Fe, Cr, Ni, and Mo; The Ni content is 0.090 mass% or less, 2. The titanium material for producing metal foil according to claim 1, wherein the content of Mo is 0.5 to 1.2 times the total content of Fe, Cr, and Ni, on a mass basis.

4. In mass percent, Sn: 0.2% or more and 2.0% or less, Zr: 0.2% or more and 5.0% or less, and Al: 0.2% or more and 3.0% or less, and one or more of the group consisting of, is contained in a total amount of 0.2% or more and 5.0% or less, N: 0% or more and 0.100% or less, C: 0% or more and 0.080% or less, H: 0% or more and 0.0150% or less, O: 0% or more and 1.000% or less, and 2. The titanium material for manufacturing metal foil according to claim 1, containing Fe: 0% or more and 0.500% or less.

5. Contains more than 1.8% by mass and 7.0% by mass or less of Al, When the content of Al is [Al%], the content of Zr is [Zr%], the content of Sn is [Sn%], and the content of O is [O%], the following formula (1) is satisfied:

2. The titanium material for producing metal foil according to claim 1, wherein the Al equivalent Al represented by formula (1) is 7.0 mass% or less.

6. The titanium material for producing metal foil according to any one of claims 1 to 5, which is a titanium material for use in a drum for producing metal foil.

7. A process for producing a titanium ingot by a continuous casting method in which a molten titanium material is poured into a coolable mold having an open top and bottom, the surface of the molten titanium material in the mold is heated, and the material is cooled and solidified through the mold while the solidified material is pulled downward using a jig; a step of heating the titanium ingot to a temperature of 750° C. or higher but lower than the β transformation point, and rolling the titanium ingot to a rolling reduction of 90% or higher to produce a rolled plate; The method includes a step of performing a heat treatment at a temperature of 600° C. or more and 750° C. or less for a time of 20 minutes or more and 120 minutes or less, cooling from the heat treatment temperature to 500° C. at an average cooling rate of 20° C. / min or more, and cooling from the heat treatment temperature to a temperature of 300° C. or less at an average cooling rate of 10° C. / min or less, The titanium material comprises, in mass %, Sn: 0% or more and 2.0% or less, Zr: 0% or more and 5.0% or less, Al: 0% or more and 7.0% or less, N: 0% or more and 0.100% or less, C: 0% or more and 0.080% or less, H: 0% or more and 0.0150% or less, O: 0% or more and 1.000% or less, Fe: 0% or more and 0.500% or less, Cr: 0% or more and 0.500% or less, Ni: 0% or more and 0.090% or less, Cu: 0% or more and 1.5% or less, and Mo: 0% or more and 0.750% or less; The balance has a chemical composition consisting of Ti and impurities, The total content of Fe, Cr, and Ni is 0% or more and 0.500% or less; A manufacturing method for titanium material for manufacturing metal foil.

8. hot working the titanium ingot to produce a slab; 8. The method for producing a titanium material for use in producing a metal foil according to claim 7, wherein in the step of producing the rolled plate, the slab is rolled instead of the titanium ingot.

9. the casting means is an electron beam melting method; The amount of electron beam irradiation into the internal space of the mold in the electron beam melting method is 150 W / cm 2 9. The method for producing a titanium material for producing a metal foil according to claim 7 or 8, wherein the titanium material has a melting rate of 2.5 ton / h or less, and the material is melted by irradiating the electron beam.

10. X in cm is the ratio of the horizontal cross-sectional area of ​​the internal space of the mold to the circumferential length of the inner circumference in the horizontal cross section of the mold, and W / cm is the irradiation dose of the electron beam in the electron beam melting method. 2 Y is represented by the following formula (2): Y=-3.8X+(135±25)...Formula (2) The method for producing a titanium material for use in producing metal foil according to claim 9, wherein the following relationship is satisfied:

11. The casting method is a plasma melting method, The plasma irradiation dose into the mold in the plasma melting method was 380 W / cm 2 9. The method for producing a titanium material for producing metal foil according to claim 7 or 8, wherein the melting rate of the titanium material is 2.5 ton / h or less, and the material is melted by irradiating the plasma.

12. The horizontal section of the space inside the mold is expressed in cm. 2 The method for producing a titanium material for producing metal foil according to any one of claims 7 to 11, wherein the ratio of the area to the perimeter in cm is 7.5 cm or more and 22.5 cm or less.

13. The titanium material for producing metal foil according to claim 6, which is attached along the outer circumferential surface of a cylindrical inner drum; and a weld disposed at the butt joint of the titanium material.

Citation Information

Patent Citations

  • Production of titanium or titanium alloy sheet free from macropattern

    JP1997176809A

  • Titanium for copper foil production drum having excellent surface layer part structure and production method therefor

    JP2002285267A

  • Titanium for copper foil production drum having uniform metallic structure and production method therefor

    JP2002322526A

  • TITANIUM PLATE FOR DRUM FOR USE IN PRODUCING ELECTROLYTIC Cu FOIL AND MANUFACTURING METHOD THEREFOR

    JP2009041064A

  • Titanium alloy sheet for drum for producing electrolytic copper foil with sheet surface texture developed, and method for manufacturing the same

    JP2012112017A